Network security attacks and countermeasures - Kumar G., Dileep, 1982-; Singh, Manoj Kumar, 1972-; Jayanthi, M. K., 1976-; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, PA 17033, USA) : IGI Global, 2016)
"This book discusses the security and optimization of computer networks for use in a variety of disciplines and fields, touching on such matters as mobile and VPN security, IP spoofing, and intrusion detection"--Provided by publisher.
Introduction to network security / C. V. Anchugam, K. Thangadurai -- Security Issues in mobile wireless networks / Arif Sari -- Virtual private networks / Alok Vishwakarma -- Classification of network attacks and countermeasures of different attacks / C. V. Anchugam, K. Thangadurai -- Attacks in wireless sensor networks / George William Kibirige, Camilius A. Sanga -- Sensors network: in regard with the security aspect and counter measures / Mamta Bachani, Ahsan Memon, Faisal Karim Shaikh -- DDoS attacks and their types / Dileep Kumar -- Cluster-based countermeasures for DDoS attacks / Mohammad Jabed Morshed Chowdhury, Dileep Kumar G -- Intrusion detection system (IDS) and their types / Manoranjan Pradhan, Chinmaya Kumar Nayak, Sateesh Kumar Pradhan -- Intrusion prevention system / Bijaya Kumar Panda, Manoranjan Pradhan, Sateesh Kumar Pradhan -- AdaBoost algorithm with single weak classifier in network intrusion detection / P. Natesan, P. Balasubramanie, G. Gowrison -- Countering RSA vulnerabilities and its replacement by ECC: elliptic curve cryptographic scheme for key generation / Behnam Rahnama, Arif Sari, Marwan Yassin Ghafour -- Changing dynamics of network security involving hacking/cracking with next generation firewalls (NGFW) / Alok Vishwakarma, Wafa Waheeda S.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 01/30/2016).
Keywords: Computer networks -- Security measures; Computer crimes -- Prevention; DDoS attacks; Intrusion detection and prevention; Network administration; RSA vulnerabilities; Threat classification; Virtual private networks; VPN security; Wireless sensor networks; Electronic books